Curbing crop residue burning to improve public health and reduce emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
CCAFS, CIMMYT, the CGIAR Research Program on Wheat and partners provided science-based evidence to the Indian Government on crop residue burning. This encouraged the Indian Government to prioritize crop residue management solutions, and establish a large-scale routing investment of USD 170 million (INR 1150 crores).